2021
DOI: 10.1002/cam4.3913
|View full text |Cite
|
Sign up to set email alerts
|

Income loss after a cancer diagnosis in Germany: An analysis based on the socio‐economic panel survey

Abstract: Background and Aims Cancer treatments often require intensive use of healthcare services and limit patients’ ability to work, potentially causing them to become financially vulnerable. The present study is the first attempt to measure, on the German national level, the magnitude of absolute income loss after a cancer diagnosis. Methods This study analyzes data from the Socio‐Economic Panel (SOEP) survey, one of the largest and most comprehensive household surveys in Germany, consisting of approximately 20,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…The negative effect of a cancer diagnosis on income is already established in the literature,21 22 with some evidence on specific cancers such as breast cancer 23 24. Literature suggests that the increase in part-time contracts and the reduction of working hours as explanations for the loss in income 22 25 26. However, in our case, the income reduction does not seem to be related to an increase in part-time contracts as the analyses performed on the subsample of full-time workers confirm the overall trend.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The negative effect of a cancer diagnosis on income is already established in the literature,21 22 with some evidence on specific cancers such as breast cancer 23 24. Literature suggests that the increase in part-time contracts and the reduction of working hours as explanations for the loss in income 22 25 26. However, in our case, the income reduction does not seem to be related to an increase in part-time contracts as the analyses performed on the subsample of full-time workers confirm the overall trend.…”
Section: Discussionmentioning
confidence: 85%
“…The negative effect of a cancer diagnosis on income is already established in the literature,21 22 with some evidence on specific cancers such as breast cancer 23 24. Literature suggests that the increase in part-time contracts and the reduction of working hours as explanations for the loss in income 22 25 26.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, there is also a financial burden on patients arising from out-of-pocket costs for DS that cannot be ignored. Many cancer patients suffer from financial hardship as a consequence of their illness due to diverse additional costs [ 42 ], a reduction in working hours [ 43 ], a loss of revenue and an increased likelihood of unemployment [ 43 ]. Around 20–30% of cancer survivors do not return to the workplace [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant body of recent literature examining the financial and social impact of a cancer diagnosis on patients and their families related to cancer treatment and follow-up care. These studies have shown impacts related to out-of-pocket costs (OOPC) [1–7], lost income for patients [8–14,15 ▪ ,16,17,18 ▪ ,19 ▪ ] or both [20–23,24 ▪ ,25,26,27 ▪ ,28–30]. In some cases, studies are focused on specific cancers including breast [4,18 ▪ ,22,23,31], colorectal [22,23,32,33], lung [22,23], prostate [3,22,23,25], other solid tumours [16,21,34] as well as hematologic malignancies [26].…”
Section: Recent Updates On Patients’ Financial Burden/toxicitymentioning
confidence: 99%
“…The objective of this article is to provide a summary of recent literature regarding the factors that influence access to care in cancer, with a particular focus on economics and sociocultural factors. This is a rapid review of the literature published in the past (12)(13)(14)(15)(16)(17)(18) months related to patient and family financial burden or financial toxicity. The review includes articles that examine these issues from an ethnic or cultural lens, including those populations who are identified as marginalized, and those with low education or low socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%